Extraction and concentration of glutathione from yeast by membranes. (19th March 2021) - Wang, Yiran; Xiao, Tonghu; Zhang, Zhigen; Feng, Xianshe
Abstract: This study dealt with extraction of glutathione from yeast using hot water, followed by membrane separations. The supernatant of the yeast extract was subjected to ultrafiltration (UF) to remove macromolecules, and the glutathione in the resulting ultrafiltrate was concentrated using a nanofiltration (NF) membrane. The relationships between the permeation flux and volume concentration ratio (VCR) were investigated, and the resistance of the membrane fouling layer was analyzed. This study also investigated the effects of hot water extraction conditions (e.g., temperature and time) on the glutathione yield, as well as the stability of glutathione when exposed to light. The research findings suggest that the integrated UF and NF process is a promising approach to concentrating and purifying glutathione from yeast extract. Abstract : Extraction/concentration of glutathione from yeast.